2018
DOI: 10.1093/alcalc/agy054
|View full text |Cite
|
Sign up to set email alerts
|

Distilled Spirits Overconsumption as the Most Important Factor of Excessive Adult Male Mortality in Europe

Abstract: Spirits consumption is a major risk factor of adult male mortality, with significantly greater impact compared to beer and wine. Therefore, reduction in distilled spirits consumption in hard liquor drinking areas should be a major target in health policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 67 publications
0
21
0
2
Order By: Relevance
“…Households with more men spend a larger part of their budget on spirits. Studies for other Central and Eastern Europe countries also showed that men consume spirits more frequently, in larger quantities, and with a higher percentage of pure alcohol than women do [8,9].…”
Section: First-stage Regression-quality Elasticity Of Total Expenditurementioning
confidence: 97%
See 4 more Smart Citations
“…Households with more men spend a larger part of their budget on spirits. Studies for other Central and Eastern Europe countries also showed that men consume spirits more frequently, in larger quantities, and with a higher percentage of pure alcohol than women do [8,9].…”
Section: First-stage Regression-quality Elasticity Of Total Expenditurementioning
confidence: 97%
“…Considering a specific group, percentages were 30%, 21%, 39% for spirits, wine, and beer, respectively. The percentages indicated a high level of alcoholic-beverage consumption, which could be a sign of a higher percentage of people with addiction and related health problems [3,7,8].…”
Section: Descriptive Statisticsmentioning
confidence: 98%
See 3 more Smart Citations